Pengaruh Variasisilica Fumedan Perubahan Faktor Air Semen Terhadap Modulus Elastisitas Beton - Setyo H., Nor Intang (Jenderal Soedirman University, 2005)
The aim of this research is to know influence of addition silica fume and variation of water cement ratio (w/c), also interaction of between both to elasticity modulus of concrete. Independent variable in this research is variation of silica fume and water cement ratio. Dependent variable is compression strength and strain for result of elasticity modulus. The sample test of cylinder concrete with diameter 15 cm and high 30 cm, with the variation of w/c 0,3 ; 0,35 ; 0,4 ; 0,45 ; and 0,5, and also variation of silica fume 0,5%, 10%, 15%, and 20% cement weight. Each treatment made by 10 samples with of volume comparison of mixer concrete 1 : 1,5 : 2,5. The result of samples test carried out 28th days of age obtained optimum rate silica fume 9,328% with w/c 0,35 giving influence to increase of concrete elasticity modulus of concrete to 4,191% of normal concrete